Social responsability in vocational guidance in Argentina - Andrea Ferrero (Universidad de San Buenaventura, 2009)
The beginning of the vocational guidance in Argentina was based on detecting personal characteristics regarding working abilities, and many social aspects were considered in the assessment process. In this country, increasing social exclusion as a product of poverty, lack of opportunities, unemployment and poor level of education, have introduced new aspects in vocational guidance considerations related to this new set of high level structural complexity. The professional responsibility in providing vocational guidance in such context is analyzed considering two kinds of sources: ethical standards of psychology, and specific competencies of vocational guidance.